Wasan the fascination of traditional Japanese mathematics - Sakurai, Susumu 1968-; Ford, Emma; Sekimori, Gaynor; Sakurai, Susumu 1968- (2018)
"Wasan--a unique form of Japanese mathematics--was developed during the Edo period (1603-1868), a time when the entire country was isolated from the rest of the world. Mathematics was enjoyed as a form of entertainment by adults and children alike and by people of all social classes. Jink?oki, an extraordinary mathematics textbook, was used at private elementary schools called terakoya and became a bestseller that could be found in every household. Furthermore, world-class works were produced by Japanese mathematicians such as Seki Takakazu and Takebe Katahiro. This book explores the beauty and fascination surrounding wasan by providing a guided tour that goes back in time over three hundred years and navigates through the mysterious and incredible world of mathematical wizardry found during the Edo period in Japan"--Dust jacket.
Mathematics fever -- Wasan enthusiasts and ? [pi] -- Wasan, alive today -- Exercises.
"This book is a translation of 'Much?u ni naru! Edo no s?ugaku' (Shueisha Inc., 2012) which was originally published under the title 'Edo no s?ugaku ky?okasho' by Shueisha International Inc. in 2009"--Title page verso.
Text in English.
Keywords: Mathematics, Japanese